The Effect of Durian (Durio zibethinus) Seeds and Albedos Extract on Reducing Cholesterol Levels - Maharani, Lila; Mahbubah, Fina Saffanatul; Habib, Ismul Mauludin Al (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to determine the potential of durian to reduce cholesterol levels. This research used a completely randomised design as the basis for determining the sample size. There were 5 treatment groups, including durian seed extract (T1), durian albedo extract (T2), a combination of seed and albedo extract (T3) and those 3 treatment groups were given at a dose of 0.28 mg/head/day, quail eggs at a dose of 0.5 mL/head/day, and cholesterol reducing medication at 50 mg/head/day. The data were analyzed using the One Way ANOVA Test, which showed that p (0.004) < 0.05, leading to the conclusion that there was a real differences between all treatment groups. The seed extract group experienced the largest average decrease, namely 49.15 mg/dL, while the average decrease in the combination seed-albedo extract group and cholesterol reducing medication was 43.0 mg/dL, 33.4 mg/dL, and 28.7 mg/dL, respectively. The conclusion of this research is durian seed extract and albedo are effective in reducing cholesterol levels in the blood.